If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.33x + 1 = 9 Reorder the terms: 1 + 0.33x = 9 Solving 1 + 0.33x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 0.33x = 9 + -1 Combine like terms: 1 + -1 = 0 0 + 0.33x = 9 + -1 0.33x = 9 + -1 Combine like terms: 9 + -1 = 8 0.33x = 8 Divide each side by '0.33'. x = 24.24242424 Simplifying x = 24.24242424
| -5(x-3)=15(x-7)+2 | | 1.75x=8 | | 5-(x-3)=6-2x | | 5-x=4x-60 | | 7x-2x=8-3x | | 3x+8=-4x+8 | | -4x-1=-1+7x | | 4x-12=-7x+10 | | 5x-x=3x-2 | | -x+3=23 | | -2x-6=16 | | x^3-12= | | 7x-(3x+6)=5x-47 | | 5x^2+1=2x | | 2y^3-7y^2+3=0 | | 50x^2+1=2x | | 6x-7x-5=0 | | 16x-282=6x-12 | | 52-6x=12x+18 | | 9x-(7x+2)=3x-22 | | 6x+22=16x-98 | | 3x^2+2x-40=0 | | 3x^2+58x-40=0 | | 3x^2+119x-40=0 | | x^2+25x-24=0 | | 2x+125=6x+93 | | (x)(x+1)(x+2)=720 | | 2x+25=6x+93 | | 3x^2-29x-10=0 | | x^4-4x^2+12x+9= | | x^4-4x^2+12x+9=0 | | 3x+2.3=5x+1.7 |